Formation of mucus-permeable nanoparticles from soy protein isolate by partial enzymatic hydrolysis coupled with thermal and pH-shifting treatment. (1st January 2023) - Yuan, Dan; Zhou, Feibai; Niu, Zhicheng; Shen, Penghui; Zhao, Mouming
Graphical abstract: Highlights: A new strategy was developed to fabricate mucus-permeable soy protein nanoparticles (SPNPs). Heating and pH-shifting after proteolysis modulated the size and surface charge of SPNPs. Smaller size and less negatively charged SPNPs exhibited higher mucus permeability. The formation of SPNPs was related to the assembly behavior of typical subunits. Loose structure facilitated the assembly of subunits upon pH-shifting. Abstract: Modulating the size and surface charge of nanocarriers provides an efficacious strategy to enhance bioavailability of encapsulated cargos through increased mucus penetration. In this study, mucus-permHeable soy protein nanoparticles (SPNPs) were successfully fabricated via gastrointestinal proteolysis coupled with heating and pH-shifting treatment. Results showed that treatment at 65 °C and 75 °C after proteolysis induced the assembly of α, ά, and β subunits, forming a relatively loose structure. This facilitated further assembly upon pH-shifting, forming smaller-sized and less electronegative nanoparticles, which showed enhanced mucus permeability. However, treatment at 85 °C and 95 °C promoted stronger hydrophobic interactions and induced disulfide bond cross-linking between B and β subunits, forming compact macro-aggregates with high β -sheet structure. These larger-sized aggregates were less influenced by pH-shifting treatment, demonstrating limited mucus diffusion. This study provides a potential alternative to fabricate mucus-permeable nanoparticles, and established a relationship between protein subunit assembly behavior and its mucus permeability.